FISCAL AFTERSHOCKS: TAXES AND CATASTROPHES IN CHILEAN HISTORY. (September 2022) - Gil, Magdalena; Atria, Jorge
ABSTRACT: Socio-natural disasters remain underexplored events in economic history, even though they stress societies in several ways and are known for their relationship with institutional change. In this paper, we explore this issue showing that major earthquakes in Chile have become a window of opportunity for important fiscal reforms. Our findings indicate that there are two mechanisms to explain this relationship: first, reconstruction demands greater state expenditure and intervention; and second, the emergence of narratives that justify these reforms, such as patriotism and solidarity. However, data show that in the case of Chile, changes following disasters have had little impact on the overall tax structure of the country, and the historical preference for indirect taxes has been maintained, with limited power to impose taxes on high-income groups.